2010
DOI: 10.1007/s00432-010-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of WIF-1 in hepatocellular carcinomas

Abstract: WIF-1 silencing as a result of its promoter hypermethylation may be a frequent event in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Aberrant methylation of promoter regions that silence gene transcription has been recognized as a mechanism for inactivating tumor suppressor genes in some cancers [31,32]. WIF-1 silencing due to promoter methylation has also been recognized to facilitate tumorigenesis in nasopharyngeal and lung cancer, hepatocellular carcinoma, and colorectal cancer [33][34][35][36][37]. Considering this, we speculate that promoter hypermethylation is the key factor to affect the function of WIF-1 in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aberrant methylation of promoter regions that silence gene transcription has been recognized as a mechanism for inactivating tumor suppressor genes in some cancers [31,32]. WIF-1 silencing due to promoter methylation has also been recognized to facilitate tumorigenesis in nasopharyngeal and lung cancer, hepatocellular carcinoma, and colorectal cancer [33][34][35][36][37]. Considering this, we speculate that promoter hypermethylation is the key factor to affect the function of WIF-1 in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…As a key antagonistic gene in the Wnt/β-catenin signaling pathway, WIF-1 inhibits the upstream of Wnt/β-catenin signal transduction by binding to Wnt proteins [13]. Downregulation of WIF-1 expression has been detected in various adult cancers [16][17][18][19][20]. However, the expression and molecular function of WIF-1 remains unknown in pediatric cancer, especially in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for WIF-1 loss during hepatocarcinogenesis (72). Inactivity of the negative Wnt regulators Dkk2 and Dkk3 has been reported in human gastrointestinal tumours (73).…”
Section: Wnt/β-catenin Signalling and Cancermentioning
confidence: 99%
“…Although it remains possible that a functional sequence polymorphism exists outside the flanking regions analyzed, a more likely scenario is that SV235 carries an epiallele within its noncoding cly1 sequence, which has the effect of alleviating the repression of cly1 transcription. Such epialleles within transcriptional regulatory regions have been repeatedly associated with gene silencing in both plant and mammalian genomes (Shibuya et al 2006;Kinoshita et al 2007;Deng et al 2010;Ecker 2013). In rice, a genome-wide scan of DNA methylation has indicated that CpG methylation is rarest within regions stretching from slightly upstream to some 500 nt downstream of the transcriptional start site (Zemach et al A Novel Epiallele of cly1 in Barley 101 2010).…”
Section: Dna Methylation Within Cly1b2 Represses Transcriptionmentioning
confidence: 99%